The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2337/db11-0506
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation During Working Memory Is Altered in Patients With Type 1 Diabetes During Hypoglycemia

Abstract: OBJECTIVETo investigate the effects of acute hypoglycemia on working memory and brain function in patients with type 1 diabetes.RESEARCH DESIGN AND METHODSUsing blood oxygen level–dependent (BOLD) functional magnetic resonance imaging during euglycemic (5.0 mmol/L) and hypoglycemic (2.8 mmol/L) hyperinsulinemic clamps, we compared brain activation response to a working-memory task (WMT) in type 1 diabetic subjects (n = 16) with that in age-matched nondiabetic control subjects (n = 16). Behavioral performance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 49 publications
6
54
0
Order By: Relevance
“…Regions identified as: A = ventromedial prefrontal cortex (vmPFC); B = orbitofrontal cortex (OFC); C = right ventral striatum/caudate; D = right insula; E = ventrolateral prefrontal cortex (vlPFC); F = dorsolateral prefrontal cortex (dlPFC); G = angular gyrus. example, we did not observe hypoglycemia-induced changes in the hypothalamus, which has been reported by some groups (25), but not others (42) to be altered during hypoglycemia in T1DM individuals. Thus, our findings must be interpreted cautiously given that we are only observing a snapshot of the dynamic brain changes produced over the course of falling blood glucose levels, a critical time for prevention of hypoglycemia-induced brain injury.…”
Section: Discussionsupporting
confidence: 48%
“…Regions identified as: A = ventromedial prefrontal cortex (vmPFC); B = orbitofrontal cortex (OFC); C = right ventral striatum/caudate; D = right insula; E = ventrolateral prefrontal cortex (vlPFC); F = dorsolateral prefrontal cortex (dlPFC); G = angular gyrus. example, we did not observe hypoglycemia-induced changes in the hypothalamus, which has been reported by some groups (25), but not others (42) to be altered during hypoglycemia in T1DM individuals. Thus, our findings must be interpreted cautiously given that we are only observing a snapshot of the dynamic brain changes produced over the course of falling blood glucose levels, a critical time for prevention of hypoglycemia-induced brain injury.…”
Section: Discussionsupporting
confidence: 48%
“…Indeed, studies have demonstrated an association between diabetes and a variety of brain alterations including depression, age-related cognitive decline, Alzheimer's disease, and Parkinson's disease (2,3). In addition, individuals with both type 1 and type 2 diabetes have been shown to have a variety of abnormalities in brain imaging, including altered brain activity and connectivity by functional MRI (4,5), altered microstructure by diffusion tensor imaging (6, 7), and altered neuronal circuitry in the striatum (8). Conversely, patients with Alzheimer's disease show signs of central insulin resistance with increased insulin receptor substrate (IRS) 1 serine phosphorylation in the brain and decreased insulin concentrations in the cerebrospinal fluid (9,10).…”
mentioning
confidence: 99%
“…Indirect evidence for this notion is provided by a nested case-control study showing that patients with T1DM with at least one severe episode of hypoglycemia during follow-up tended to be at lower risk of cardiovascular events, including strokes, than patients without such events (33). A recent report found that hypoglycemia caused less regional brain deactivation during working memory tasks in patients with T1DM and recurrent hypoglycemia than in healthy subjects (34). The authors interpreted this as a form of cerebral inefficiency, in that the patients needed to engage more brain regions to preserve cognitive function during hypoglycemia.…”
Section: Figurementioning
confidence: 99%